Improving service quality for parking lot users using intelligent parking reservation policies - Doulamis, Nikolaos D.; Protopapadakis, Eftychios E.; Lambrinos, Lambros (My University, 2013)
Various smart parking solutions have recently become available. They typically utilize specific technological components in their operations including RFID and various other sensors. The information gathered using such means can be processed to provide useful indicators (e.g. parking occupancy) which can be exploited by both the operators as well as the drivers. In this paper, we propose an intelligent parking reservation management architecture which is based on an optimization strategy that exploits interval scheduling principles. The aim is to improve service quality for the drivers while increasing parking lot utilization.
Keywords: Parking availability; Parking infrastructures; Parking sensors; Scheduling algorithms